Association of Serum Alpha-Tocopherol and Retinol with the Extent of Coronary Lesions in Coronary Artery Disease. (11th December 2018) - Miranda, Carolinne Thaísa de Oliveira Fernandes; Duarte, Victor Hugo Rezende; Cruz, Marina Sampaio de Menezes; Duarte, Mychelle Kytchia Rodrigues Nunes; de Araújo, Jéssica Nayara Góes; Santos, Ayda Maria Quirino Silva dos; Oliveira, Juliana Marinho de; Paiva, Maria Sanali Moura Oliveira; Rezende, Adriana Augusto; Hirata, Mario Hiroyuki; Hirata, Rosario Dominguez Crespo; Ribeiro, Karla Danielly da Silva; et al.
Abstract : Background and aims : Fat-soluble vitamins play an important role in the pathogenesis of cardiovascular disease and progression of atherosclerosis. This study aimed at investigating the relationship of the serum levels of alpha-tocopherol and retinol with the extent of coronary lesions in patients with coronary artery disease. Methods . Patients with coronary artery disease (n = 177 ) aged 30–74 years, who underwent their first coronary angiography, were enrolled. The extent of coronary lesions was assessed using the Friesinger index (FI). Accordingly, patients were grouped as follows: FI = 0–4 (n = 90 ), FI = 5–9 (n = 50 ), and FI = 10–15 (n = 37 ). Serum levels of vitamins were ‬determined via high-performance liquid chromatography and serum biochemical analysis. Results . Assessment of FI-based groups revealed that 50.8% patients had a coronary artery lesion to a low extent (FI 0–4). Individuals in this group were younger and had lower glucose and serum alpha-tocopherol levels than the other groups (p < 0.05 ). Low levels of alpha-tocopherol were more frequent in the FI 0–4 group than that in the other groups (p = 0.03 ). No difference was observed between the mean serum retinol levels among the FI-based groups (n = 0.492 ), and the low frequency of retinol was consistent among the FI groups (n = 0.348 ). Conclusions . The low level of alpha-tocopherol together with the presence of dyslipidemia is probably associated with the initial events in atherosclerosis. Increased alpha-tocopherol levels in patients with more extensive coronary artery lesions may have resulted from altered vitamin E metabolism with increased oxidative stress.